Determination of the tube voltage from clinic mammo-graphic system using two types of detectors (Brazilian Journal of Radiation Sciences (BJRS), 2015)
The use of X rays for diagnostic radiology is very common and important to Medicine, including mammographic diagnosis focusing decreasing of the doses applied to the patients and preserving high quality of the diagnostic image. A quality control program of the irradiation systems it is necessary to control periodically the performance of the X-ray systems applied in that diagnosis in order to obtain the best results in that diagnosis. The verification of the beam characteristics is made by using standard dosimetric procedures which include the determination of  the kilovoltage and the kerma rates for the different radiation qualities applied in the diagnosis. The Instruments Calibration Laboratory (LCI) of IPEN perform calibration in dosemeters used in radiation dosimetry (in diagnostic radiology) for many years and are improving their methodology to attend the actual demand of that equipments used in quality control of that X-radiation systems. The objective of that paper were the measurements of  kVp and air kerma produced for one mammographic system of LCI, Model VMI – Graphmammo AF (Philips) using two different measurements systems from PTW (Diavolt) and Radcal (kVp meter) that procedure is just to determine the stability of that system that is used to perform diagnosis in mammography level. The results obtained with the two systems utilized shows good agreement. That measurement can be applied at a routine quality control program of that X-ray system.